ECONOMETRIC ANALYSIS OF FACTORS AFFECTING EXTERNAL LABOR MIGRATION (Scientific electronic journal "Labor Economics and Human Capital", 2023)
In this article, an econometric analysis of the factors influencing the processes of external labor migration was carried out. The influence of the number of deductions on external labor migration, real total income per capita, the number of births and the unemployed was scientifically analyzed, dependencies were studied and appropriate conclusions and proposals were made.
Keywords: external migration, unemployment, income, birth, divorce, model, variables, standard of living, family, factors, assessment.